Aterosclerose assintomática em síndrome de sjogren primária - Garcia, Ana Beatriz Andreo [UNIFESP] (2016)
Objectives: To evaluate subclinical atherosclerosis in patients with Sjögren syndrome using non-invasive methods.Patients and methods: We assessed traditional risk factors such as hypertension, diabetes, dyslipidemia, smoking and family history of atherosclerosis. Patients with prior cardiovascular events and a history of atherosclerosis were excluded. Clinical and laboratory features were recorded, as well as the EULAR Sjogren?s Syndrome Activity Index (ESSDAI) calculation. The atherosclerosis evaluation was done by carotid intima-media thickness (CIMT), measured by ultrasonography, and ankle brachial index (ABI).Results: Fifteen patients (31%) had at least one traditiona risk factor and 65.3% had an ESSDAI score from mild to moderate. Only two patients had increased CIMT. However, 60% presented ABI alterations. The Multiple Correspondence Analysis (MCA) showed a clear correlation between low ABI and the positivity of autoantibodies (ANA, anti-SSA, RF). Conclusions: The subgroup of patients with positive autoantibodies is at a higher risk of early atherosclerosis, which indicates the need for more careful monitoring in this group.